2017
DOI: 10.3945/ajcn.117.161356
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of global nutrient profiling systems for restricting the commercial marketing of foods and beverages of low nutritional quality to children in Canada

Abstract: The Canadian government recently committed to introduce legislation to restrict the commercial marketing of unhealthy foods and beverages to children. We compared the degree of strictness and agreement between nutrient profile (NP) models relevant to marketing restrictions by applying them in the Canadian context. With the use of data from the University of Toronto 2013 Food Label Information Program ( = 15,342 prepackaged foods), 4 NP models were evaluated: the Food Standards Australia New Zealand-Nutrient Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
67
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 22 publications
10
67
0
2
Order By: Relevance
“…In the absence of any formative food composition data, it is imperative to test how foods available in Jamaica perform using different NPSs. Other countries have compared how different NPSs might apply to the products available in their country, such as in Canada [24,25], Mexico [26] and Colombia [27]. The findings here on the share of products with excess NOCs under the PAHO compared to the Chile NPS are consistent with the studies done elsewhere; the PAHO NPS would identify a larger percentage of packaged products as having excess NOCs.…”
Section: Discussionsupporting
confidence: 84%
“…In the absence of any formative food composition data, it is imperative to test how foods available in Jamaica perform using different NPSs. Other countries have compared how different NPSs might apply to the products available in their country, such as in Canada [24,25], Mexico [26] and Colombia [27]. The findings here on the share of products with excess NOCs under the PAHO compared to the Chile NPS are consistent with the studies done elsewhere; the PAHO NPS would identify a larger percentage of packaged products as having excess NOCs.…”
Section: Discussionsupporting
confidence: 84%
“…This research suggests that the nutrient criteria and narrow scopes on marketing techniques covered in policies are some of the potential loopholes. The nutrient criteria delimit the products that are allowed to be marketed to children, therefore week standards will result in higher exposure of HFSS food and beverage products as previous research have demonstrated [57][58][59][60]. On the other hand, narrowing the scope to a single marketing technique and/or media channels, settings and platforms leaves room for food and beverage companies to continue to market HFSS food and beverage products to young people.…”
Section: Discussionmentioning
confidence: 99%
“…Foods in FLIP 2013 were classified into 24 major and 153 minor categories as defined in the Table of Reference Amounts for Foods (TRA) in the Food and Drug Regulations, which provides detailed examples of the types of foods in each category and subcategory [19]. The identification of products displaying M2K on the packaging has been previously determined in FLIP 2013, based on the display of at least one of the following persuasive marketing techniques: children's product lines (e.g., junior, mini); child-appealing lettering, images or graphics; allusions to fun or play; unconventional flavors, colors, or shapes; toys, coupons, prizes, or contests; games; and child-appealing characters [20].…”
Section: Methodsmentioning
confidence: 99%